The feasibility and safety of adopting the left lumbar vein to localize the renal artery location during left transperitoneal laparoscopic partial nephrectomy - Yao, Zhongshun; Zhao, Jiming; Zheng, Bin; Cong, Zixiang; Zhang, Yiming; Lv, Jiaju; Niu, Zhihong; Cheng, Fajuan; He, Wei (Frontiers in Surgery, 2022)
Background: Laparoscopic partial nephrectomy (LPN) is the standard of care for localized small renal cancer. The most critical step in this surgery is to seek the renal artery. In the present study, we describe a novel technique with the left lumbar vein (LV) to access the left renal artery during LPN. Material & Methods: A retrospective review of 130 cases of transperitoneal laparoscopic partial nephrectomies (TLPN) was performed for patients with renal cancer in our center from January 2018 and December 2021. The lumbar vein (LV) or non-lumbar vein (N-LV) technique were utilized to locate and manage the left renal artery. Relevant clinical data of patients were recorded, including characteristics of patient and tumor and perioperative outcomes (artery mobilization time, operative time, estimated blood loss, complications, and so on). Comparative analysis between the lumbar vein and non-lumbar vein cases was performed. Results: All TLPNs were successfully accomplished without conversion to open approaches. There were no complications involving renal vessels during the entire study. The use of the LV technique had a shorter artery mobilization time and less estimated blood loss (p < 0.05). There was no difference in terms of perioperative complications between the two groups. Conclusion: The left lumbar vein can represent an anatomic landmark for locating the left renal artery in TLPN. It offers the advantages of the transperitoneal approach, facilitating access to the left renal artery and shortening operation time.